Remote Access to Instrumental Analysis for Distance Education in Science - Dietmar Kennepohl; Jit Baran; Mike Connors; Kieron Quigley; Ron Currie (International Review of Research in Open and Distributed Learning, 2005)
Remote access to experiments offers distance educators another tool to integrate a strong laboratory component within a science course. Since virtually all modern chemical instrumental analysis in industry now use devices operated by a computer interface, remote control of instrumentation is not only relatively facile, it enhances students’ opportunity to learn the subject matter and be exposed to “real world” contents. Northern Alberta Institute of Technology (NAIT) and Athabasca University are developing teaching laboratories based on the control of analytical instruments in real-time via an Internet connection. Students perform real-time analysis using equipment, methods, and skills that are common to modern analytical laboratories (or sophisticated teaching laboratories). Students obtain real results using real substances to arrive at real conclusions, just as they would if they were in a physical laboratory with the equipment; this approach allows students to access to conduct instrumental science experiments, thus providing them with an advantageous route to upgrade their laboratory skills while learning at a distance.